2016
DOI: 10.1177/0271678x16635183
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal imaging of the availability of dopamine transporter and D2 receptor in rat striatum following mild ischemia

Abstract: The changes in the availability of striatal dopamine transporter and dopamine D2 receptor after mild focal ischemia in rats were measured using a small animal positron emission tomography system. Mild focal ischemia was induced by 20-minute middle cerebral artery occlusion. [11 C]PE2I binding to dopamine transporter was transiently increased on the ipsilateral side of the striatum at 2 days after middle cerebral artery occlusion. On day 7 and 14 after middle cerebral artery occlusion, [11 C]PE2I binding levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Even though we cannot infer the temporal order of events due to the cross‐sectional nature of this study, previous work suggests that reduced cerebrovascular integrity reduces DA‐system integrity. For instance, in a longitudinal animal study, induction of cerebral ischemia in rats led to reduced striatal 11 C‐raclopride binding over time . Another study showed that heart failure was followed by attenuated cerebral blood flow as well as DA levels …”
Section: Discussionmentioning
confidence: 99%
“…Even though we cannot infer the temporal order of events due to the cross‐sectional nature of this study, previous work suggests that reduced cerebrovascular integrity reduces DA‐system integrity. For instance, in a longitudinal animal study, induction of cerebral ischemia in rats led to reduced striatal 11 C‐raclopride binding over time . Another study showed that heart failure was followed by attenuated cerebral blood flow as well as DA levels …”
Section: Discussionmentioning
confidence: 99%
“…The MCAO rat model was established as in our previous studies [ 14 ], with some modifications. Briefly, rats weighing approximately 300 g were initially anesthetized with 5% isoflurane and maintained under anesthesia with 2% isoflurane (room air, 1.5 L/min).…”
Section: Methodsmentioning
confidence: 99%
“…Further, striatal selective neuronal loss (SNL) can be induced by brief MCAO without infarction, but this includes microglia and astrocyte activation [ 12 , 13 ]. In previous studies, we reported SNL at 7 days after 20-min MCAO, without acute brain infarction [ 14 ]. Taken together, these lines of evidence suggest that the activation of microglia and astrocytes after mild ischemia might be a key factor in SNL.…”
Section: Introductionmentioning
confidence: 99%
“…In the sole report describing the effect of Ovx on neuronal function in the acute stage of ischemia, Pelligrino et al (1998) observed larger reduction in neuronal power within the first 30 min following common carotid artery clamping combined with hemorrhagic hypotension in Ovx female rats compared to Sham animals. However, early neuronal dysfunction is not a reliable predictor of long term injury ( Moore et al, 2000 ; Lake et al, 2017 ; Momosaki et al, 2017 ). To develop novel therapeutic approaches, it is necessary to have a model that recapitulates the combined effect of estrogen loss and the sequelae of events following ischemia.…”
Section: Discussionmentioning
confidence: 99%